Nanoporous Anodic Alumina 3D FDTD Modelling for a Broad Range of Inter-pore Distances - Bertó-Roselló, Francesc (Springer US, 2016)
The capability of the finite difference time domain (FDTD) method for the numerical modelling of the optical properties of nanoporous anodic alumina (NAA) in a broad range of inter-pore distances is evaluated. FDTD permits taking into account in the same numerical framework all the structural features of NAA, such as the texturization of the interfaces or the incorporation of electrolyte anions in the aluminium oxide host. The evaluation is carried out by comparing reflectance measurements from two samples with two very different inter-pore distances with the simulation results. Results show that considering the texturization is crucial to obtain good agreement with the measurements. On the other hand, including the anionic layer in the model leads to a second-order contribution to the reflectance spectrum.